Current Slide

Small screen detected. You are viewing the mobile version of SlideWiki. If you wish to edit slides you will need to use a larger device.

Resolution – Complete Example

  • Equivalent proof by Resolution
    • Convert predicates to clause normal form
      Predicate form
      Clause form
      1. (x) (dog(X) animal(X))
      ¬ dog(X) animal(X)
      2. dog(fido)
      3. (Y) (animal(Y) die(Y))
      ¬ animal(Y) die(Y)
    • Negate the conclusion
      4. ¬ die(fido)                      ¬ die(fido)

Speaker notes:

Content Tools


There are currently no sources for this slide.